(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Supportive waist protection is the most used among various functional waist protection products. It achieves its supportive effect primarily through elastic-banded supportive strips, with their shape, number, and material influencing the level of support. This study assesses the subjective and objective pressure comfort of waist protection with different support strip designs, utilizing a combination of subjective pressure numerical representation and the Novel-appliance pressure testing system. The findings indicate that pressure from supportive waist protection is primarily concentrated in the posterior and lateral lumbar regions, with the lateral region experiencing greater pressure than the anterior and posterior centre regions. Moreover, pressure along the abdominal circumference line generally exceeds that along the waist circumference line. The comfortable pressure value in the posterior waist region exceeds that in the lateral and frontal regions. Finally, varying shapes, numbers, and materials of support strips result in different pressure intensities in the posterior waist region, with 4 strips of bionic material offering the best waist comfort and 4 strips of steel plate providing the least comfort.